The Secret Beyond Dalton's Dreams Travel In James Wan's Insisdious Movie (2010) A Psychoanalytic Approach - Prayogi, Imam Nur; , Dr. Phil. Dewi Candraningrum, M.Ed; , Drs. Sigit Haryanto M.Hum (2013)
This study is about the secret in insidious movie z01r}. This objective of the study is to apply the psychoanalytic approach to analyze the emotional and character building in insidious movie' The writer use Freud's major point of psychoanalytic to answer the problem of the study. The study is descriptive qualitative research which data are taken from script of insidious movie. The technique of analyzing data is descriptive The study oomes to the fullowing conclusion. First, based on the struetural analysis of each elements, it shows that the character an characterization' plot' setting, point of view, theme, casting, mise en scene, cinematograPhY, sound, and editing are related to each other and from the unity. Second, based on the psychoanalytic analysis, human has different psychology. The psychology is based on different id, ego and super ego. Human has a freedom to choose and then responsible for the psychology. The responsibility will appear an anxiety' James Wan wants to convey a moral message that human has to believe each other and we are not live alone in this world'.